2018
DOI: 10.1007/s00276-018-2028-y
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and clinical analysis of the distal ulna and extensor carpi ulnaris tendon using MRI

Abstract: The gender differences in distal ulnar measurements can be beneficial for surgery and forensic science. UG is wider than ECU tendon, and this is the cause of normal subluxation. Therefore, rather than deepening UG, surgeons should focus on tendon sheath abnormalities as a physiological solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Grade 2 was assigned if the line passed between 51% and 99% of the groove. Forearm rotation also was determined according to this drawn line (20,22,26). (Figure 3-4).…”
Section: Resultsmentioning
confidence: 99%
“…Grade 2 was assigned if the line passed between 51% and 99% of the groove. Forearm rotation also was determined according to this drawn line (20,22,26). (Figure 3-4).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, Toprak et al suggested that it may be more beneficial to focus on the damage of the subsheath rather than deepening the groove, as a result of their findings that showed the groove is wider than the ECU tendon in anatomically normal individuals. 6 Our study was limited by the fact that our subjects were fresh frozen cadavers rather than living human subjects, as well as the small sample size of 12 cadavers. Our power calculation indicated that a sample size of 22 would achieve sufficient statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Toprak et al suggested that it may be more beneficial to focus on the damage of the subsheath rather than deepening the groove, as a result of their findings that showed the groove is wider than the ECU tendon in anatomically normal individuals. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Two distal ulnar dimensions: the ulnar distal end width (UDEW) defined as the largest ulnar width at its distal end (Monum et al, 2021). The ulnar styloid process length (USPL) is the vertical distance between the styloid tip and the ulnar styloid process base (Toprak and Turkoglu, 2018)  Reliability assessment: The reliability of the measurements of the RDEW, RH, UDEW, and USPL was assessed by comparing the mean values of the two researchers' readings at different times and in different situations using the paired (t) test, Pearson correlation coefficient, and scatter plot chart to outline the correlation between the two researchers' readings concerning the numerical values of the studied dimensions. The dimensions that were found to be reliable were then validated.…”
mentioning
confidence: 99%